Analisis Efektivitas Sistem Filtrasi Multi Media sebagai Komponen Infrastruktur Hijau dalam Peningkatan Kualitas Air Kolam Renang - Trisno Fallo Fallo; Nurhadi; Faras Dessyana Nurullisa; Doni Anggara (Universitas Proklamasi 45, 2026)
The growing demand for sustainable urban water management has encouraged the integration of treatment technologies into green infrastructure systems. This study evaluates the effectiveness of a multi-media filtration system as a component of green infrastructure in improving swimming pool water quality based on physicochemical parameters. The filtration media consisted of silica sand, activated carbon, and zeolite arranged in a layered configuration. An experimental approach was applied by analyzing turbidity, pH, and iron (Fe) concentration before and after filtration. The results indicate that the system significantly reduced turbidity by up to 79.6% and iron concentration by approximately 80%, while stabilizing pH within acceptable standards. These findings demonstrate that multi-media filtration is not only effective as a water treatment method but also has strong potential to be integrated into green infrastructure frameworks. The system contributes to environmental sustainability by supporting water reuse and reducing pollution load. Therefore, this approach can be considered a viable solution for enhancing urban environmental quality through adaptive and low-cost technology.